Type 2 diabetes after a pregnancy with gestational diabetes among first nations women in Australia: The PANDORA study. (November 2021) - Wood, Anna J.; Boyle, Jacqueline A.; Barr, Elizabeth L.M.; Barzi, Federica; Hare, Matthew J.L.; Titmuss, Angela; Longmore, Danielle K.; Death, Elizabeth; Kelaart, Joanna; Kirkwood, Marie; Graham, Sian; Connors, Christine; et al.
Highlights: This is the first prospective study of type 2 diabetes among First Nations women after gestational diabetes (GDM). First Nations Australian women with GDM have a high cumulative incidence of type 2 diabetes (22%) 2.5 years postpartum. Risk for postpartum diabetes includes age, multiparity, higher glucose values, insulin use and body mass index (BMI). We highlight a need for policies on postpartum screening developed in partnership with First Nations women with GDM. Abstract: Aims: To determine among First Nations and Europid pregnant women the cumulative incidence and predictors of postpartum type 2 diabetes and prediabetes and describe postpartum cardiovascular disease (CVD) risk profiles. Methods: PANDORA is a prospective longitudinal cohort of women recruited in pregnancy. Ethnic-specific rates of postpartum type 2 diabetes and prediabetes were reported for women with diabetes in pregnancy (DIP), gestational diabetes (GDM) or normoglycaemia in pregnancy over a short follow-up of 2.5 years (n = 325). Pregnancy characteristics and CVD risk profiles according to glycaemic status, and factors associated with postpartum diabetes/prediabetes were examined in First Nations women. Results: The cumulative incidence of postpartum type 2 diabetes among women with DIP or GDM were higher for First Nations women (48%, 13/27, women with DIP, 13%, 11/82, GDM), compared to Europid women (nil DIP or GDM p < 0.001). Characteristics associated with type 2 diabetes/prediabetes among First Nations women with GDM/DIP included, older age, multiparity, family history of diabetes, higher glucose values, insulin use and body mass index (BMI). Conclusions: First Nations women experience a high incidence of postpartum type 2 diabetes after GDM/DIP, highlighting the need for culturally responsive policies at an individual and systems level, to prevent diabetes and its complications.